1996
DOI: 10.1007/bf00403965
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary sodium on blood pressure in IDDM patients with nephropathy

Abstract: The objectives of the study were to assess the effects of moderate sodium restriction on blood pressure in insulin-dependent diabetic (IDDM) patients with nephropathy and high normal or mildly hypertensive blood pressure (primary objective), and to document possible associated changes of exchangeable body sodium, body volumes, components of the renin-angiotensin-aldosterone system, atrial natriuretic peptide, and catecholamines (secondary objective). Sixteen patients with untreated systolic blood pressure > or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Salt restriction reduced the volume of distribution of the HTc]DTPA, which is a marker of the extracellular volume status. This is supported by a recent study in human diabetes that demonstrated a significant correlation between urinary sodium excretion and plasma volume (38). Therefore, salt restriction in experimental diabetes may result in a decrease in the extracellular volume and in stimulation of the RAS, leading to a fall in atrial natriuretic peptide (ANP) release from the heart (39,40).…”
Section: Discussionmentioning
confidence: 78%
“…Salt restriction reduced the volume of distribution of the HTc]DTPA, which is a marker of the extracellular volume status. This is supported by a recent study in human diabetes that demonstrated a significant correlation between urinary sodium excretion and plasma volume (38). Therefore, salt restriction in experimental diabetes may result in a decrease in the extracellular volume and in stimulation of the RAS, leading to a fall in atrial natriuretic peptide (ANP) release from the heart (39,40).…”
Section: Discussionmentioning
confidence: 78%
“…It has been argued that the clear benefits of additional BP lowering demands a low-sodium diet in all patients with diabetes [5]. At the same time, RAAS activation is clearly increased with sodium restriction in diabetic patients [33], and the wide clinical utility and effects of drugs that block the RAAS [3] stand as testament to the importance of this pathway in diabetes, beyond its actions on BP regulation. In addition, we have previously been unable to observe any association between sodium intake and BP indices in patients with either Type 1 or Type 2 diabetes after adjusting for age and gender, with or without antihypertensive treatment [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is too early to draw final conclusions because of lack of long-term (Ͼ4 weeks) studies with a moderate reduction in sodium intake (about 100 mmol/24 h). Blood lipid levels were only investigated in 2 to 5 long-term studies with a mean sodium reduction of 75 mmol/24 h. 26,43,56,57,87 The evidence from these was not statistically significant. The effect on the lipid profile may be secondary to a shift in fluid balance such as hemoconcentration; in the present study this premise is supported by a significant body weight reduction of about 1 kg in the sodium-reduced group, probably reflecting a decrease in total body water.…”
Section: Commentmentioning
confidence: 98%